Criminal legislation in the context of urisprudential disputes - Siavash Goodarzi; Mohammad Ebrahim Shamsnateri (مطالعات فقه و حقوق اسلامی)
Legislation based on Imami jurisprudence has led to the richness and independence of our rights in decades of legislation. There has always been a debate about what criteria should be used to legislate according to jurisprudence And typically the focus has been on who or what is being followed And it is enough to provide general criteria and in practice there is no decisive criterion for this issue. This article discusses only the criminal law and the specific conditions and requirements of the law in this regard Because it is not possible to provide a standard for legislation on all laws with specific conditions and characteristics of each of them Because the law in each case can be very different from the law in other area And you have to think about each case according to its specific requirements And refrained from generalizations and providing a standard for all cases. This article seeks to provide an appropriate solution in the field of criminal law And prevented the entry of personal opinions and ideas into the field of legislation And as far as possible our criminal law Closer to the world criminal law without distancing itself from its originality.